Everything She Touches, Changes Remix: Feminist New Materialism and Contemporary Magical Futurist Art - Hale, Amy (Approaching religion, 2025)
This article explores a group of contemporary magical artists who are inspired by feminist new materialist thought. In the work of these contemporary artists, magic is defined less by the transmission of traditions and initiatory wisdom or revelations about truth, and more by the ways in which artists can initiate change by shifting perspectives and orientations through creating inspiring, affective, embodied experiences. I argue that the philosophical shifts that are emerging from feminist philosophies and feminist fiction are also helping to create a cultural space for wider discussions of magic, particularly among artists, who are reconfiguring ideas about nature and being, erasing the distinctions between the human and non-human worlds, highlighting the deep connections between the material and immaterial.